2022
DOI: 10.1101/2022.03.08.22271816
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerosolized Ad5-nCoV booster vaccination elicited potent immune response against the SARS-CoV-2 Omicron variant after inactivated COVID-19 vaccine priming

Abstract: The SARS-CoV-2 Omicron variant has become the dominant SARS-CoV-2 variant around the world and exhibits immune escape to current COVID-19 vaccines to some extent due to its numerous spike mutations. Here, we evaluated the immune responses to booster vaccination with intramuscular adenovirus-vectored vaccine (Ad5-nCoV), aerosolized Ad5-nCoV, a recombinant protein subunit vaccine (ZF2001) or homologous inactivated vaccine (CoronaVac) in those who received two doses of inactivated COVID-19 vaccines 6 months prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“… 17 19 Another two booster vaccination studies illustrated that the pseudo-virus neutralizing antibody titers against wild-type SARS-CoV-2 strain and Omicron variant elicited by ZF2001 booster following two-dose inactivated vaccines were 2.2–3.3-fold and 1.6–2.5-fold higher, respectively, than those induced by a homologous booster of inactivated vaccines. 20 , 21 A nationwide cohort study conducted in Sweden showed that the effectiveness against symptomatic COVID-19 infection was 67% and 79% for the heterologous ChAdOx1/BNT162b2 and ChAdOx1/mRNA-1273 prime-boost vaccinations, respectively, which were higher than 50% of the homologous ChAdOx1 vaccination. 14 The preliminary analysis results of a phase III clinical trial demonstrated that after a heterologous booster vaccination of the recombinant protein subunit vaccine V-01 in inactivated vaccine recipients, the person-year incidence rate of SARS-CoV-2 infections was reduced from 12.80% to 6.73%, and the absolute protective efficacy was 61.35% ( https://en.livzon.com.cn/companyfile/1029.html ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 17 19 Another two booster vaccination studies illustrated that the pseudo-virus neutralizing antibody titers against wild-type SARS-CoV-2 strain and Omicron variant elicited by ZF2001 booster following two-dose inactivated vaccines were 2.2–3.3-fold and 1.6–2.5-fold higher, respectively, than those induced by a homologous booster of inactivated vaccines. 20 , 21 A nationwide cohort study conducted in Sweden showed that the effectiveness against symptomatic COVID-19 infection was 67% and 79% for the heterologous ChAdOx1/BNT162b2 and ChAdOx1/mRNA-1273 prime-boost vaccinations, respectively, which were higher than 50% of the homologous ChAdOx1 vaccination. 14 The preliminary analysis results of a phase III clinical trial demonstrated that after a heterologous booster vaccination of the recombinant protein subunit vaccine V-01 in inactivated vaccine recipients, the person-year incidence rate of SARS-CoV-2 infections was reduced from 12.80% to 6.73%, and the absolute protective efficacy was 61.35% ( https://en.livzon.com.cn/companyfile/1029.html ).…”
Section: Discussionmentioning
confidence: 99%
“… 11 13 Besides the homologous boosting, heterologous booster strategy has also attracted great concerns, and multiple clinical trials and cohort studies have shown that the immune response elicited by heterologous prime-booster vaccination was significantly greater than that induced by homologous counterparts. 14 21 Currently, several clinical trials have been conducted to evaluate the safety, immunogenicity and efficacy of a heterologous booster dose of recombinant subunit vaccines, such as V-01 (NCT05096832), ZF2001 (NCT05205096, NCT05205083) and SCB-2019 (NCT05087368), following two-dose inactivated vaccines. Some preliminary study results have demonstrated that the heterologous booster of recombinant protein subunit vaccines distinctly improved the neutralizing antibody level 17 21 and protective efficacy ( https://en.livzon.com.cn/companyfile/1029.html ) against various SARS-CoV-2 strains, including the Omicron variant, which was immunogenically superior to the homologous booster of inactivated vaccines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarizes the geometric mean titer (GMT) following homologous and heterologous vaccination against different COVID-19 variants in the current studies (63,(72)(73)(74)(75)(76)(77)(78). It is noteworthy that levels of neutralizing antibodies produced in populations receiving a heterologous booster after two doses of inactivated viral vaccines are higher than that of the homologous group.…”
Section: Booster Vaccination Strategymentioning
confidence: 99%
“…More than 250 COVID-19 vaccines are currently being developed,4 and over 90 vaccines are developed in the middle and late clinical research stages 5. At present, there are three kinds and five brands of COVID-19 vaccines approved for listing with conditions in China: inactivated vaccines (produced by Beijing Institute of Biological Products and Wuhan Institute of Biological Products under China Biotechnology of China Pharmaceutical Group, and Sinovac Biotech), adenovirus vector vaccine (produced by CanSino Biologics) and recombinant COVID-19 vaccine (produced by Zhi Fei Long Ke Ma Biopharmaceutical) 6 7. Most of the approved COVID-19 vaccines are in emergency use or listed with conditions, and the data on the effectiveness of the vaccines are mainly derived from clinical trial results 8–23.…”
Section: Introductionmentioning
confidence: 99%